Isolated angiitis of central nervous system with pleocytosis in the cerebrospinal fluid. Issue 867 (January 1998) - Ferraz, H. B.; Rolim, J. A.; Neves, A. C.; Augusto, L.; Andrade, F.; Rodrigues, J. F.; Stavale, J. N.
Abstract : We report the case of a 32-year-old woman with isolated angiitis of the central nervous system. This case shows that high levels of pleocytosis may not rule out isolated angiitis of the central nervous system if this diagnosis can be considered on clinical grounds.